Request for adjustment of contract price for the unreasonable hike due to pandemic and war situation - Tritech ACMV Engineering Company (Brac University, 2023)
This record consists of general correspondence regarding the request for adjustment of contract price of BRACU new campus project for the unreasonable hike due to pandemic and war situation.